PROIECTUL „FAC CE VREAU, DAR ȘTIU CE FAC” LA BIBLIOTECA „OVIDIUS” - CEBANU, șef oficiu, Filiala „Ovidius”, Victoria (BIBLIOPOLIS, 2020)
The Project I do what I want, but I know what I’m doing presented by the Ovidius Branch at the FedEx days aimed to cultivate a responsible behavior of users in order to develop, maintain and fortify the mental and physical health. The project includes a cycle of meetings Talking with psychologist, Dr. Ludmila Bolboceanu, specialist of the Department of professional education from the Ministry of Education of the Republic of Moldova. The project duration – from December 2014 to May 2015 includes six sessions. The target group selected from the students of the „Mihai Viteazul” theoretical School belongs to the risk group of teenagers. The subjects was selected after an opinion pool, elaborated by the “Ovidius” Branch.          The project highlights the problems needed to be analyzed and solved: the problem of physical violence, developing of the young individuality, sexual education etc. However, the project reveals the desire to know and to read the books form the collection of Ovidius Branch, recommended by the specialist.